A multicentre study to predict neonatal survival according to lung‐to‐head ratio and liver herniation in fetuses with left congenital diaphragmatic hernia (CDH): Hidden mortality from the Latin American CDH Study Group Registry. (15th May 2019) - Cruz‐Martínez, Rogelio; Etchegaray, Adolfo; Molina‐Giraldo, Saulo; Nieto‐Castro, Belen; Gil Guevara, Enrique; Bustillos, Joaquin; Martínez‐Rodríguez, Miguel; Gámez‐Varela, Alma; Saldivar‐Rodríguez, Daniel; Chávez‐González, Erendira; Keller, Rodolfo; Russo, Ricardo; et al.
Abstract: Objective: To evaluate natural history of fetuses congenital diaphragmatic hernia (CDH) prenatally diagnosed in countries where termination of pregnancy is not legally allowed and to predict neonatal survival according to lung area and liver herniation. Methods: Prospective study including antenatally diagnosed CDH cases managed expectantly during pregnancy in six tertiary Latin American centres. The contribution of the observed/expected lung‐to‐head ratio (O/E‐LHR) and liver herniation in predicting neonatal survival was assessed. Results: From the total population of 380 CDH cases, 144 isolated fetuses were selected showing an overall survival rate of 31.9% (46/144). Survivors showed significantly higher O/E‐LHR (56.5% vs 34.9%; P  < .001), lower proportion of liver herniation (34.8% vs 80.6%, P  < .001), and higher gestational age at birth (37.8 vs 36.2 weeks, P  < 0.01) than nonsurvivors. Fetuses with an O/E‐LHR less than 35% showed a 3.4% of survival; those with an O/E‐LHR between 35% and 45% showed 28% of survival with liver up and 50% with liver down; those with an O/E‐LHR greater than 45% showed 50% of survival rate with liver up and 76.9% with liver down. Conclusions: Neonatal mortality in CDH is higher in Latin American countries. The category of lung hypoplasia should be classified according to the survival rates in our Latin American CDH registry